The cost of warfarin treatment for stroke prevention in patients with non-valvular atrial fibrillation in Mexico from a collective perspective. (4th March 2017) - Briere, Jean Baptiste; Bowrin, Kevin; Wood, Robert; Holbrook, Tim; Roberts, Jenna
Abstract: Aims: To describe the collective costs of vitamin K antagonist (VKA) treatment for stroke prevention in non-valvular atrial fibrillation (NVAF). VKA drug costs are relatively low, but they necessitate frequent international normalized ratio (INR) monitoring. There are currently minimal data describing the economic impact of this in Mexico. Materials and methods: Cardiologists provided data on their NVAF patients ( n = 400) to quantify direct medical costs (INR testing, appointments, drug costs). A sub-set of patients ( n = 301) completed a patient questionnaire providing data to calculate direct non-medical costs (travel and other expenses for attendance at VKA-associated appointments) and indirect costs (opportunity cost and reduced work productivity associated with VKA treatment). Results: Estimated annual direct medical costs totaled 753.6 per patient. Annual direct non-medical and indirect costs were USD149.8 and 132.1, respectively. Limitations: Recruited patients were those who consulted with a cardiologist during the study period and selected due to inclusion criteria. All had received uninterrupted treatment for 12–24 months. Consequently, the results are not fully generalizable to all VKA treated NVAF patients. Conclusions: The true cost of VKA treatment cannot be appreciated by a consideration of drug costs alone. Ongoing monitoring appointments incur additional expenses for both patients and the healthcare system.